Mechanical energy and kinematics of double poling technique performed at different inclines by world-level cross-country skiers during World Cup races - Canclini, A.; Canclini, A.; Baroni, G.; Lindinger, S.; Pozzo, R. (Journal of Science in Sport and Exercise, 2021)
Purpose: To analyze the inter-limb coordination patterns and energy recovery of elite cross-country skiers performing double poling (DP). Methods: Thirty-three elite athletes in three track sections of FIS-WC races, with different slopes (2°, 0° and - 1.5°). Stereo vision capture system (50 Hz cameras) and 3D analysis were used to extract: kinematic parameters (center of gravity, velocity); joint angles and angular velocities; energy (potential and kinetic) and energy recovery indices R% and R(t) during the entire DP cycle and within poling (Rpol) and swing phase (Rswi). Results: Average race velocity of the centre of gravity (Vave) significantly varied according to slopes (5.4, 7.3 and 8.3 m/s). This correlated with differences in the angular velocities of the most relevant joints. Elbow flexion angular velocity in the early portion of poling phase was higher according to the slope variations (- 137, - 171 and - 202 deg/s, for the slopes 2°, 0° and - 1.5°, respectively), indicating the possible modulation of muscular stretch shortening cycle (SSC). A similar trend was observed for shoulder angular velocity which increased during poling phase, and for knee extension velocity during swing phase, and for knee extension velocity during swing phase. R% decreased significantly for the - 1.5° slope (32% and 24% vs. 15%); R(t) was higher for the Rswi. Significant differences were observed in trunk-elbow, trunk-shoulder, trunk-knee and elbow-shoulder patterns for the - 1.5° slope with respect to the others. Conclusions: Despite the modest variation of the track`s slope, the effects on propulsion and recovery strategies were different.